1963
DOI: 10.1039/tf9635901248
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational frequency assignment and molecular structure of p-benzoquinone

Abstract: The infra-red absorptions of p-benzoquinone (O=C6H4=O) have been studied in the vapour, solution and solid phases. Measurements were made in the range 5000-200 cm-1: In conjunction with published Raman spectra and our own infra-red spectra for a number of simple derivatives, including deutero-bcnzoquinone (O=C,sD4=O) and the di-imine (HN=Cs-=NH), a complete assignment of the fundamental modes is presented. A self-consistent m.0. calculation of the bonding conditions is brie5y reported.As expected, the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…26,30,31 The assignment of this spectrum, in particular that of the pair of intense bands at 1650-1670 cm…”
Section: Theoretical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,30,31 The assignment of this spectrum, in particular that of the pair of intense bands at 1650-1670 cm…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…This spectrum is in excellent accord with previous measurements in the gas and in condensed phases. 26,30,31 The assignment of this spectrum, in particular that of the pair of intense bands at 1650-1670 cm À1 , which appear prominently in the matrix spectrum, had been controversial, because calculations predict only one fundamental in this region. However, it was established that the two bands which are peaking at 1659 and 1671 cm À1 in our matrix spectra are due to two Fermi-coupled b 1u vibrational states.…”
Section: Vibrational Structure Of Pbqmentioning
confidence: 99%
“…The recommended frequencies in ref 10 are composed of the experimental spectra of gaseous and liquid p-Qu as well as its spectra in various solvents, 25,26 wherein, the change of solvent leads to a significant change in the frequencies of p-Qu. 27,28 At the same time, the calculations by the authors themselves 10 according to the use of valenceforce field 29−31 showed a significant discrepancy between the theoretical frequencies and ω exp measured in the liquid phase, specifically for the high amplitude motion. In work 32, the farinfrared spectrum of gaseous p-Qu was measured.…”
Section: Experimental Details and Calculationsmentioning
confidence: 99%
“…As noted before, they calculated the entropy S ° , the heat capacity C p , the reduced enthalpy ( H T 0 – H 0 0 )/ T and the reduced free energy −( G T 0 – H 0 0 )/ T within the scope of the RRHO model in the range 273.15–1500 K (Supporting Information) using this set of frequencies. The recommended frequencies in ref are composed of the experimental spectra of gaseous and liquid p -Qu as well as its spectra in various solvents, , wherein, the change of solvent leads to a significant change in the frequencies of p -Qu. , At the same time, the calculations by the authors themselves according to the use of valence-force field showed a significant discrepancy between the theoretical frequencies and ω exp measured in the liquid phase, specifically for the high amplitude motion. In work , the far-infrared spectrum of gaseous p -Qu was measured.…”
Section: Experimental Details and Calculationsmentioning
confidence: 99%
“…The assignments of the neat capping materials are discussed in section 3 of the Supporting Information. The spectrum of AuNR@CTAB (Figure a) manifested most of the characteristics of CTAB, with some residual absorbances, which might be attributed to the most intense bands of the CC stretch mode (red fragment at ∼1515 cm –1 ) of the reactant hydroquinone and the CO stretch mode (green fragment at ∼1680 cm –1 ) of the oxidation product p -benzoquinone in the synthesis. Some weak bands were buried at 1300–1000 cm –1 .…”
mentioning
confidence: 99%